Mirror-Less Unidirectional Radiation in an Asymmetric Single Resonator - Song, Joohyung; Heo, Hyungjun; Lee, Sangjun; Kim, Sangin (Journal of Lightwave Technology, 2022)
We propose a novel approach to realize unidirectional radiation in an asymmetric single resonator without using an external mirror, which is based on mutual coupling between two degenerate resonant modes through the background scattering of the asymmetric resonator. In the proposed approach, only one of the resonant modes experiences optical gain and the other works just as an internal reflector. So, our approach is conceptually to mimic a one-port system by introducing the internal reflector in a two-port system. Due to this intuitive and simple operation concept, the design of such devices is straightforward. We described the operation principle by using the temporal coupled-mode theory, from which a practical design method was derived. An example device of the proposed approach was designed based on guided-mode resonances in a slab waveguide grating and its performance was analyzed with the finite-difference time-domain simulation. A ratio of 4.6 x 104 between the upward and the downward radiations was numerically demonstrated.
Keywords: External mirrors; Guided-mode resonance; Internal reflectors; Intuitive operations; Mutual coupling; Resonant mode; Slab; Surface-emitting laser; Unidirectional radiation; Zero-contrast grating; Guided-mode resonance; surface emitting lasers; unidirectional radiation; zero-contrast gratings